Single‐Molecule Analysis of the Recognition Forces Underlying Nucleo‐Cytoplasmic Transport1. Issue 39 (5th September 2013) - Rangl, Martina; Ebner, Andreas; Yamada, Justin; Rankl, Christian; Tampé, Robert; Gruber, Hermann J.; Rexach, Michael; Hinterdorfer, Peter
<x xml:space="preserve">Abstract</x> Transport forces: To move molecules across the nuclear envelope they have to overcome the selective barrier of the nuclear pore which is formed by nucleoporins (nups) with FG repeats. The molecules are chaperoned by shuttling receptors that interact with FG nups thereby passing the barrier using an unresolved mechanism. This process is explored by single‐molecule force spectroscopy (see picture).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>